2022
DOI: 10.3389/fnsyn.2022.889947
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Non-Associative Long-Term Potentiation in Immature Granule Cells in the Dentate Gyrus of Adult Rats

Abstract: The dentate gyrus is one of the few sites of neurogenesis in the adult brain. Integration of new-generated granule cells into the hippocampal circuitry provides a substrate for structural plasticity, fundamental for normal function of adult hippocampus. However, mechanisms of synaptic plasticity that mediate integration of new-generated granule cells into the existing circuitry remain poorly understood. Especially mechanisms of plasticity at GABA-ergic synapses remain elusive. Here, we show that postsynaptic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Because synapses undergoing LTD were not stimulated during the induction, this form of LTD was called heterosynaptic. Moreover, heterosynaptic plasticity, both LTP and LTD, could be induced in cortical neurons by episodes of strong postsynaptic activity alone, without stimulation of any synapses during the induction [15,16,43,[22][23][24][25][26][27][28]42]. Local forms of heterosynaptic plasticity include induction of LTP and LTD around the location of the tetanized synapses, forming a Mexican hat-shaped profile of plastic changes [17][18][19], and spread of plastic changes to non-stimulated synapses of the same neuron, or even to closely located but nonstimulated neurons [20,21].…”
Section: Homosynaptic and Heterosynaptic Plasticity Terminologymentioning
confidence: 99%
See 2 more Smart Citations
“…Because synapses undergoing LTD were not stimulated during the induction, this form of LTD was called heterosynaptic. Moreover, heterosynaptic plasticity, both LTP and LTD, could be induced in cortical neurons by episodes of strong postsynaptic activity alone, without stimulation of any synapses during the induction [15,16,43,[22][23][24][25][26][27][28]42]. Local forms of heterosynaptic plasticity include induction of LTP and LTD around the location of the tetanized synapses, forming a Mexican hat-shaped profile of plastic changes [17][18][19], and spread of plastic changes to non-stimulated synapses of the same neuron, or even to closely located but nonstimulated neurons [20,21].…”
Section: Homosynaptic and Heterosynaptic Plasticity Terminologymentioning
confidence: 99%
“…Plastic changes induced by such purely postsynaptic protocol can be interpreted as heterosynaptic. Intracellular tetanization paradigm has been applied to study plasticity in diverse cells and preparations: pyramidal neurons in the hippocampus [16], granular neurons of the dentate gyrus [22], excitatory and inhibitory neurons of the neocortex [23][24][25][26][27][28],…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Li et al (2012) reported that development of GABAergic inputs controls the contribution of maturing neurons to the adult hippocampal network and define the memory representations ( Li et al, 2012 ). Simonova et al (2022) proposed that potentiation-based non-associative plasticity of GABAergic transmission might help to counter-balance an increase of excitatory drive that is facilitated by enhanced LTP at the glutamatergic synapses in maturing granule cells ( Simonova et al, 2022 ). The selective regulation of the plasticity potential of the granule cells of different ages determines how the hippocampal network stores and maintains memories.…”
Section: Introductionmentioning
confidence: 99%
“…Plastic changes induced by such a purely postsynaptic protocol can be interpreted as heterosynaptic. The intracellular tetanization paradigm has been applied to study the plasticity in diverse cells and preparations, including pyramidal neurons in the hippocampus [17], granular neurons of the dentate gyrus [24], excitatory and inhibitory neurons of the neocortex [25][26][27], and even identified neurons of the common snail [28], but has never been tested in in vivo preparations. In contrast to in vitro preparations, evidence for heterosynaptic plasticity in vivo is sparse, in part because of difficulties in controlling for the absence of presynaptic stimulation during plasticity induction.…”
Section: Introductionmentioning
confidence: 99%